Efektivitas Model Pembelajaran Jigsaw dan Numbered Head Together (NHT) dalam Pemecahan Soal-Soal HOTS Materi Pokok Fungsi Komposisi - Debi Cinta Marito Ritonga; Faisal Faisal; Raudhatul Husna (Prodi Pendidikan Matematika, Fakultas Tarbiyah dan Ilmu Keguruan IAIN Langsa, 2022)
The study was intended to learn the effectiveness of jigsaw's and Numbered Heads Together (NHT) learning models in breaking the matter of HOTS composition function in Muhammadiyah high school Langsa from; The results of student learning after using the jigsaw model and Numbered Heads Together (NHT), student activity and teacher activity during the learning process, and student response to the learning model. This type of research is qualitative. The subject of this study was the Langsa Muhammadiyah high school student at X MIPA class with a total of 25 students. The data collection techniques used are tests, observations, and angkets. As for the data analysis used by the study results test analysis, the student activity and teacher activity data analysis, and the student response analysis. The results of the study were 88% of all students completed after the application of the jigsaw model and Numbered Heads Together (NHT) to complete the HOTS matter composition function. On student activities in the learning process the average percentage is 81.75% high in category, then on teacher activity gets an average of each category (RTK) rated within good criteria with an average score of 4.0. And finally, students response after learning shows an average percentage of 77.6%, it shows that students respond favorably to the applied learning model. We can then conclude that the jigsaw and other competing heads together learning models are effectively used to solve the HOTS matter of composition function.